Bāṃlādeśe samājatantrera patha : jātīẏa gaṇatāntrika biplaba (Kendrīẏa Kamiṭi, Bāṃlādeśera Kamiunisṭa Pārṭi, 1980)
Program of action of the Communist Party of Bangladesh, adopted at the 3rd Congress of the Party, Dacca, 1980.